-12+5n=21+-6n

Simple and best practice solution for -12+5n=21+-6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12+5n=21+-6n equation:


Simplifying
-12 + 5n = 21 + -6n

Solving
-12 + 5n = 21 + -6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6n' to each side of the equation.
-12 + 5n + 6n = 21 + -6n + 6n

Combine like terms: 5n + 6n = 11n
-12 + 11n = 21 + -6n + 6n

Combine like terms: -6n + 6n = 0
-12 + 11n = 21 + 0
-12 + 11n = 21

Add '12' to each side of the equation.
-12 + 12 + 11n = 21 + 12

Combine like terms: -12 + 12 = 0
0 + 11n = 21 + 12
11n = 21 + 12

Combine like terms: 21 + 12 = 33
11n = 33

Divide each side by '11'.
n = 3

Simplifying
n = 3

See similar equations:

| 25p=p+15 | | 4y=-6x+5 | | 25+p=p-15 | | 8x-5=7x+70 | | -1=4-p-5 | | 10+p=p-15 | | 4(2-8r)=-34 | | k/12=-8 | | 112+38y=512+58y | | 10+p=p-5 | | 5x^6+40x^5+75x^4=0 | | -x^2+.25x=0 | | 5+4y=8 | | 7y-1=-8y-20 | | 6+-4=x | | 8x^2-16x+17=0 | | 20-p=p | | -3n-2(6-4n)=21-6n | | 20-p=p+0.25 | | 20-p=p+0.5 | | 15-p=p+2 | | 15-p=p+1 | | -8u+36=-2(u+3) | | 20-p=p+1 | | 35f+2=4-15f | | 20-p=p+2.5 | | .32*.4= | | 20-p=p+5 | | 0.75x+3.82=20.32 | | 20-p=p+10 | | -7+-4=x | | 4.5q=32.4 |

Equations solver categories